Lightning induced overvoltage and protection scheme for DC fourth rail transit insulation coordination - Farah Asyikin Abd Rahman, Dr. (2023)
The LRT Kelana Jaya line is one out of only three direct current (DC) urban light rail transit systems in the world that employ fourth rail technology. The fourth rail traction technology came to light as a post development of the third rail traction technology. It provides a solution to the stray current setback that third rail technology cannot handle. The difference between fourth rail and third rail technology is that the fourth rail refrains from using the running rails as the return circuit, thus avoiding the stray current issue. To ensure reliable operation of the transit, it is necessary to investigate lightning transients on the system, and design effective protection measures against lightning. It is important to really emphasise this matter to the Malaysian authorities, even though the reported incidents concerning the transit being struck by lightning are few, but the likelihood of it to be struck is never nil. This is especially true as the system is built and operated in the heart of Kuala Lumpur, a city that is ranked as having the fifth highest lightning activity in the world. In this study, the section of the route between Setiawangsa Station and Damai Station was selected as a case subject. The electrical performance and effectiveness of the insulated rail brackets and the station surge arresters were studied and compared with a reference case scenario through Electromagnetic Transients Program Restructured Version (EMTP-RV) software simulation under both steady state and lightning induced overvoltage conditions. The results demonstrated that the Glass Reinforced Plastic (GRP) material for the insulated rail brackets showed a better coordination with the station arresters compared to the Cast Epoxy (CE) material when impressed by a lightning channel base current, especially a lightning current with high magnitude. In addition, for fact-finding purposes the GRP bracket was simulated with an unrelated arrester, known as the PDTA09 arrester. The results showed that this new insulation coordination managed to further reduce the clamping magnitude of the lightning induced overvoltage in comparison with the coordination between the CE bracket and the 3EB4-010 station arrester, for at least 20 %. It is well understood that when an arrester clamps the induced overvoltage at a lower magnitude, this signifies the arrester has quick speed-of-response compared to if the arrester clamped a little later which would make the arrester clamp at a higher magnitude and thus jeopardise the downstream equipment. These findings have significant implications for the targeted DC transit system, especially in areas with high levels of lightning activities. It would be wise to take this information into account when designing any new DC transit projects or improving existing networks by setting the proper insulation coordination affairs.